Palm-coein classification of abnormal uterine bleeding and clinicohistopathological correlation - Vasava, Vimal H.; Airao, Bhavesh B.; Shingala, Milan R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The aim was to categorize women with AUB as per the PALM-COEIN classification system as this is a step towards cause based diagnosis and focused management of patients. The acronym PALM-COEIN comes from arranging basic categories of the classification system. The PALM group comprises the structural entities, which can be measured visually or by using imaging techniques and histopathology. The COEIN group comprises the non- organic types which cannot be defined by imaging or histopathology. Methods: The study comprised 350 women of reproductive age with AUB for minimum 3 month time span. It describes and observes AUB in amount, interval and frequency for women attending out-patient Gynaecology department of C. U. Shah Medical College and Hospital, Surendranagar (Gujrat) over a period of 1year from November 17 to October 18. They were assessed on the basis of structured history, physical examination, local pelvis examination, investigations, USG findings and endometrial histopathological report. Cause of AUB was determined and treatment was given to the patient as appropriated by categorization done in agreement with the PALM-COEIN classification. Results: The most prevalent cause of AUB was ovulatory dysfunction (n=99, 28.2%). Next common cause was leiomyoma (n=90, 25.7%), followed by endometrial causes (n=52, 14.5%), adenomyosis (n=30, 8.5%) not yet classified (n=32, 9.7%), malignancy and hyperplasia (n=28, 8.1%), polyp (n=9, 2.5%), iatrogenic (n=7, 2.2%) and coagulopathy (n=1, 0.3%). Conclusions: The PALM-COEIN classification helps to practically as certain because of AUB, and there by effectively adopt the correct treatment for AUB patients.